EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PADI DAN PADI LADANG DI DESA BILA TALANG KECAMATAN TABANG KABUPATEN KUTAI KARTANEGARA - Ince Raden, Thamrin, S. Syarif (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2012)
This study aimed to determine the suitability classes of land and improvement efforts in order to develop lowland and upland rice in the Bila Tabang village of Tabang Sub District.  Survey fieldwork was conducted with making mini profile (1.2 x 1.2 x 1 m) for morphological properties of the samples that were carried out at a depth of 0-30 cm and 30-60 cm, while drilling carried around a mini profile with composite method (8 points) for the analysis of the nature of soil physic/chemical.  The data obtained were analyzed using standard criteria of the Soil Research Institute, Centre for Research and Development of Land and Agro-climate, Agricultural Research Agency, the Department of Agriculture in 2003 that use of land quality criteria which include temperature, availability of water, availability of oxygen, rooting media, nutrient retention, sodisitas, erosion and land preparation.  Each area was divided into several quality characteristics of land used as a reference to assess the characteristics of the land so that this land can be determined several factors limiting the growth of rice crops to be developed.  The survey showed that the actual land suitability classes are marginally suitable (S3) for lowland paddy as well as upland rice, but compliance can be improved through efforts to improve by adding the organic matter, fertilizing, liming, drainage, terracing and guludan so that potential land suitability class to be quite suitable (S2).